Phytoseius Ribaga (Mesostigmata: Phytoseiidae) in the Brazilian Espinhaço Range: seven new species, renaming of the plumifer species group, and a critical review of its taxonomic characters - Ferragut, Francisco; Navia, Denise (Zootaxa, 2024)
The mountainous regions in eastern Brazil are home to an astonishing variety of Phytoseius (Mesostigmata: Phytoseiidae) species, 11 of which were collected in surveys conducted between 2010–2012. Our study revealed a great diversity in the plumifer species-group, in which we describe seven new taxa, P. maspretiosus sp. nov., P. multilunatus sp. nov., P. trisetatus sp. nov., P. itobira sp. nov., P. dasalmas sp. nov., P. bahiensis sp. nov., and P. paucipapillatus sp. nov.. This enabled us to compare close species in this group determining valid diagnostic characters, providing a critical review of the prevailing taxonomic traits and revealing unexpected patterns in important diagnostic features based on our observations and the literature. Moreover, we claim the taxonomic importance of two morphological traits usually mentioned in previous studies, but never exploited to their full potential: the female pattern of dorsal ornamentation and the shape of the male spermatodactyl. Aware of the incongruity that the exemplar species of the plumifer group, P. plumifer (Canestrini & Fanzago), belongs to the horridus species group, we propose that the group be renamed as mexicanus-species group. A key to the Brazilian species of Phytoseius is included.